LIBRARIANS’ PREPAREDNESS IN EMERGING TECHNOLOGIES TO OFFER LIBRARY SERVICES (Contemporary Journal of Social Science Review, 2025)
Purpose- This study aimed to examine the preparedness of librarians to use emerging technologies (Augmented/virtual reality, cloud computing, semantic web/linked data, Bibliographic Framework, current awareness services, Really Simple Syndication feed, Big Data, Radio Frequency Identification, and WeChat) to offer library services (user, technical, instructional, and management services). Design/methodology/approach- A survey method of research was applied to conduct the research. A quantitative and structured questionnaire was used to collect data. The population of the study consists of library professionals of Lahore, Islamabad, and Rawalpindi (Pakistan). Convenience sampling was applied and 218 library professionals of public and private universities were taken as sample. The data was analyzed by using SPSS. Findings- Results show that most of the respondents are highly prepared to use emerging technologies to offer library services. There is no significant difference exists between various university librarians in terms of preparedness regarding emerging technologies in offering user services, technical services, technical services, and management services. Conversely, all the above emerging technologies were not used in their libraries to offer library services. Originality/value- This paper tries to highlight the preparedness of university librarians to use emerging technologies to offer library services.